Exercise physiology trails the field in sex and gender equity: a call for faster progress, higher standards, and stronger science. - Niazi, Hira; Benbaruj, Jenna; Sheel, A. William; MacNutt, Meaghan J. (Applied Physiology, Nutrition & Metabolism, 2026)
Sex and gender inequities in biomedical research are well-documented. To evaluate the recent exercise physiology literature, we systematically analyzed participants, authors, and adherence to Sex and Gender Equity in Research (SAGER) guidelines in 629 original research articles (2018–2020) across six peer-reviewed journals. Nearly half of studies (46%) included only male/men (M/M) participants, 44% were mixed, and only 8% were female/women (F/W)-only. Only 27% of authors were women, with even lower representation among senior authors (16%) and those with >2 publications (12%). Articles with women senior authors had 72% more women co-authors, and there was a dose-dependent association between women authors and F/W participants. Articles adhered to 29 (20–43)% of relevant SAGER guidelines. Over half (58%) used inaccurate or unclear sex/gender-related language, and only 10%–34% followed guidelines that support discovery of sex/gender differences. F/W-only articles were more likely than M/M-only to report (79% vs. 12%), justify (69% vs. 5%), and discuss (62% vs. 20%) their single-sex/gender status. Articles with women authors were more likely to communicate clearly about sex/gender but otherwise had similarly poor adherence to guidelines. There are likely complex reasons why male bodies and men's voices continue to be centered in exercise physiology research. Our data implicate several logistical, attitudinal, and cultural contributors that warrant investigation and intervention. Structural support and enforcement will be needed to increase F/W inclusion and align research and reporting practices with SAGER guidelines. Associations between women authors and equitable practices suggest compound benefits of investing in recruitment and retention of women researchers.